Modelling of multi-antenna wireless channels and relay based communication systems - Paul, Babu Sena (My University, 2009)
Different issues related to modelling of multi-antenna wireless channels and relay based communication systems have been investigated in this thesis. The effects of array geometry and orientation of arrays in aMIMO system have been investigated in the frame work of geometrically based one ring scattering model for a macrocellular scenario. A technique based on scattering parameters has been developed to find the channel matrix for a MIMO system, modelled geometrically from a microwave perspective, employing suitably terminated antennas acting as scatterers. The performance of a 2D2 MIMO system has also been evaluated taking mutual coupling between the antenna elements into consideration. Using geometrical based single bounce modelling, characteristics of mobile-to-mobile communication channel has been studied and analytical expressions has been derived for probability density function of angle of arrival and time of arrival of signals in terms of model parameters. A virtual MIMO system in the form of two-hop relay channels constituting two diversity paths has been investigated for bit error rate performance with selection and maximal ratio combining techniques applied at the receiver. The works reported in this thesis are expected to contribute towards the better understanding of certain issues related to modelling of multi-antenna wireless communication channels and relay based systems...
Bhattacharjee, Ratnajit
Keywords: ELECTRONICS AND ELECTRICAL ENGINEERING